2018
DOI: 10.1155/2018/7658238
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Antimicrobial Activity and Cytotoxicity of Different Nanobiotics Targeting Multidrug Resistant and Biofilm Forming Staphylococci

Abstract: Antibiotic-resistant and biofilm-forming bacteria have surprisingly increased over recent years. On the contrary, the rate of development of new antibiotics to treat these emerging superbugs is very slow. Therefore, the aim of this study was to prepare novel nanobiotic formulations to improve the antimicrobial activity of three antibiotics (linezolid, doxycycline, and clindamycin) against Staphylococci. Antibiotics were formulated as nanoemulsions and evaluated for their antimicrobial activities and cytotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…A significant reduction in cell viability was detected at high concentration (5 and 10 mg) and high temperature (900 and 1000 ℃). It has been reported that increased biocidal activity could reduce cell viability because undesirable conditions around live cells are created 33 . Notably, calcined oyster shells (2.5 mg) treated at 750℃ showed good human body compatibility with higher number of live cells, indicating that the calcined oyster shells at this level and temperature can be an alternative antimicrobial agent.…”
Section: Resultsmentioning
confidence: 99%
“…A significant reduction in cell viability was detected at high concentration (5 and 10 mg) and high temperature (900 and 1000 ℃). It has been reported that increased biocidal activity could reduce cell viability because undesirable conditions around live cells are created 33 . Notably, calcined oyster shells (2.5 mg) treated at 750℃ showed good human body compatibility with higher number of live cells, indicating that the calcined oyster shells at this level and temperature can be an alternative antimicrobial agent.…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of MTT into purple-colored formazan by viable cells would be the indicator, with the percentage cell viability measured with microplate reader at 570 nm and 630 nm. The lighter the purple color in the results after adding the MTT reagent following incubation for 4 h, the more cells were alive after the treatment [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several previous studies, the antibacterial activity of DOXY has been reported to be enhanced by encapsulation in PNPs [ 44 ]. However, similar effect on DOXY’s antitumor activity has not been tested before.…”
Section: Discussionmentioning
confidence: 99%